Phytochemical screening, antibacterial and antioxidant activities of Asparagus laricinus leaf and stem extracts - Ntsoelinyane, Polo-Ma-Abiele Hildah; Mashele, Samson (Bangladesh Journal of Pharmacology, 2014)
The aim of this study was to investigate antioxidant activities, antibacterial activities and a phytochemical constituent of Asparagus laricinus stem and leaf extracts. Determination of antibacterial activity of extracts was assessed by agar dilution method and antioxidant properties by 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay. The minimum inhibitory concentration (MIC) of the leaf was at a concentration of 0.125 mg/mL against S. saprophyticus and E. cloacae, and at a concentration of 1 mg/mL against S. aureus and B. subtilis. There was no MIC of the stem extract at any concentration. The leaf extract showed effective free radical scavenging activity (72.1%), while stem extract had low activity. Qualitative phytochemical analysis of these plant extracts revealed the presence of tannins, saponins, flavonoids and phlobatannins. The leaf extract further confirmed the presence of glycosides, steroids, ternoids and carbohydrates. Our results indicate that, A. laricinus leaf extracts have potential antimicrobial and antioxidant activities.